High frequency pulse trains from a self-starting additive pulse mode-locked all-fiber laser - Russo, Nelida Araceli (2010)
In this paper, a coupled-cavity Er doped fiber laser is experimentally developed and analyzed. The proposed scheme has the advantage of an all-fiber configuration. Two similar fiber Bragg gratings are employed as reflective components of the main cavity containing the gain medium. The second cavity is generated, in one side, by the reflective flat end of a standard fiber optic pigtail of variable length and, in the other, by one of the Bragg gratings belonging to the main cavity. Depending on the ratio between the lengths of both cavities, trains of stable and short pulses were obtained with a repetition frequency larger than the frequency of the main cavity. The repetition rate of the pulse trains experimentally obtained was as high as 780 MHz (fifteen times the main cavity frequency) and the pulse width was ~ 110 ps. Prediction of the possible repetition rates for each cavities lengths ratio and the upgrading possibilities of this laser system are analyzed.